Effect of annealing temperature on the properties of spray deposited Cu2SnS3 thin films. Issue 11 (12th August 2013) - Chalapathi, U.; Jayasree, Y.; Uthanna, S.; Sundara Raja, V.
<x xml:space="preserve">Abstract</x> Copper tin sulphide (Cu2SnS3), a promising solar cell absorber layer for thin film heterojunction solar cells, was grown onto soda‐lime glass substrates by spray pyrolysis technique. The effect of annealing Cu2SnS3 (CTS) films in sulphur atmosphere at different annealing temperatures is investigated. From X‐ray diffraction (XRD) and Raman spectra analysis, it is observed that the films exhibit polymorphism with tetragonal and monoclinic CTS phases. While the as‐deposited films and the films annealed at 400 and 450 °C are found to contain tetragonal as well as monoclinic CTS phases, the films annealed at 500 °C are found to be mostly monoclinic CTS. The crystallite size is found to increase from 15 to 40 nm with increase of annealing temperature. From energy dispersive X‐ray spectrometer (EDS) analysis, the films annealed at 400 and 450 °C are found to be near‐stoichiometric Cu2SnS3. The direct optical band gap of CTS films with dominant tetragonal phase is found to be ∼1.10 eV, while that of films with dominant monoclinic phase is found to be 0.97 eV.